1986
DOI: 10.1523/jneurosci.06-12-03492.1986
|View full text |Cite
|
Sign up to set email alerts
|

A GABAergic inhibitory component within the hippocampal commissural pathway

Abstract: Previous results from immunocytochemical and retrograde transport studies indicated that some GABAergic neurons in the hilus of the dentate gyrus may have axonal projections through the hippocampal commissure. This study has utilized a combined immunocytochemical and retrograde transport method as well as 2 anterograde electron-microscopic methods to determine the existence of this projection in rats. Combined tracer and immunofluorescence studies showed several double-labeled GABAergic neurons in the hilus co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(64 citation statements)
references
References 28 publications
2
62
0
Order By: Relevance
“…Scharfman (1995) has also demonstrated that mossy cells innervate both granule cells and GABAergic interneurons. It should also be noted for the sake of completeness that a small component of the commissural connection in the rat does appear to arise from GABAergic neurons (Ribak et al, 1986). …”
Section: Mossy Cell Projectionsmentioning
confidence: 99%
“…Scharfman (1995) has also demonstrated that mossy cells innervate both granule cells and GABAergic interneurons. It should also be noted for the sake of completeness that a small component of the commissural connection in the rat does appear to arise from GABAergic neurons (Ribak et al, 1986). …”
Section: Mossy Cell Projectionsmentioning
confidence: 99%
“…Because it is not possible to distinguish mossy cells from neighboring hilar interneurons by morphology alone on the basis of the IR-DIC image and there is no genetic or other marker that labels living mossy cells, we developed a technique to visualize mossy cells for cell-specific ablation experiments. We took advantage of the fact that mossy cells have an extensive contralateral projection (Ribak et al, 1985;Frotscher et al, 1991;Blasco-Ibanez and Freund, 1997) and most of the axons from hilar interneurons are confined to the ipsilateral side (Ribak et al, 1986). To achieve selective mossy cell labeling on the ipsilateral side, the fluorescent dye DiO was injected into the contralateral (right) hippocampus (see Materials and Methods) ( Fig.…”
Section: Prelabeling and Visualization Of Mossy Cells In Living Slicesmentioning
confidence: 99%
“…Because several dentate interneurons, including basket cells, are long-range projection cells, GABA or glutamic acid decarboxylase (GAD) immunocytochemistry cannot be used for these experiments, because of the low and variable levels of GABA and GAD immunoreactivity present in GABAergic cells with distant projections. Colchicine injections can enhance the staining, but the interpretation of any quantitative data obtained from the colchicine-treated animals would be difficult (Ribak et al, 1986;Miettinen et al, 1992;Tóth et al, 1993;Freund and Buzsáki, 1996). Therefore, we used the SPR antibody (courtesy of Dr. Shigemoto) to ascertain the posttraumatic status of the non-PV-and non-CCK-positive interneurons in the granule cell layer.…”
Section: Modification Of the Initial "Physical" Injury Pattern At Lamentioning
confidence: 99%